Bovine immunoglobulin concentrate-Clostridium difficile retains C difficile toxin neutralising activity after passage through the human stomach and small intestine. Issue 2 (1st February 1999) - Warny, M; Fatimi, A; Bostwick, E F; Laine, D C; Lebel, F; LaMont, J T; Pothoulakis, C; Kelly, C P
Abstract : Background: Bovine immunoglobulin concentrate (BIC)- Clostridium difficile is prepared from the colostrum of cows immunised against C difficile toxins and contains high concentrations of neutralising IgG antitoxin. Aims: To determine the proportion of BIC- C difficile which survives passage through the human stomach and small intestine. Methods: Six volunteers with an end ileostomy took 5 g of BIC- C difficile containing 2.1 g of bovine IgG on four occasions: alone, with an antacid, during treatment with omeprazole, and within enteric coated capsules. Results: When BIC- C difficile was taken alone, a mean (SEM) of 1033 (232) mg of bovine IgG was recovered in the ileal fluid representing 49% of the total ingested dose. Bovine IgG recovery was not significantly increased by antacid (636 (129) mg) or omeprazole (1052 (268) mg). The enteric capsules frequently remained intact or only partially opened in the ileal effluent and free bovine IgG levels were low in this treatment group (89 (101) mg). Bovine IgG recovery was higher in volunteers with shorter (less than two hours) mouth to ileum transit times (68% versus 36%, p<0.05). Specific bovine IgG against C difficile toxin A was detected in ileal fluid following oral BIC. Toxin neutralising activity was also present and correlated closely with bovine IgG levels ( r =0.95, p<0.001). Conclusion: BIC- C difficile resists digestion in the human upper gastrointestinal tract and specific anti- C difficile toxin A binding and neutralising activity was retained. Passive oral immunotherapy with anti- C difficile BIC may be a useful non-antibiotic approach to the prevention and treatment of C difficile antibiotic associated diarrhoea and colitis.